Participative Political Institutions and City Development 800-1800 - Fabian Wahl (European Historical Economics Society (EHES), 2015)
This study investigates the effect of participative political institutions (PPIs) that emerged in many central European cities from the late 13th century. The empirical analysis of the paper is based on newly compiled long-run data for the existence of different types of PPIs in 104 cities in the Holy Roman Empire. The effect of both an overall index of participativeness of political institutions as well as of the individual PPIs is tested empirically. When pooled over all periods and observations, there seems to be a significant positive overall effect of PPIs in the German-speaking area but not in the Low Countries. The study founds considerable spatial and temporal heterogeneity in the effect of PPIs. Furthermore, the effect of different types of PPIs differs substantially and in general seems to be short-lived. That is, the results show that the positive initial effect of some PPIs declined the longer they existed and over time.
Keywords: N44; N94; O10; R11; H11; D72; 330; Medieval Period; Early-Modern Period; Central Europe; City Development; Political Institutions; Early Democracy; Guilds